Novel imidazole-alkyl spacer-carbazole based fluorophores for deep-blue organic light emitting diodes: Experimental and theoretical investigation. (February 2021) - Tagare, Jairam; Boddula, Rajamouli; Yadav, Rohit Ashok Kumar; Dubey, Deepak Kumar; Jou, Jwo-Huei; Patel, Sabita; Vaidyanathan, Sivakumar
Abstract: A series of fluorescent emitters based on Imidazole-Alkyl spacer-Carbazole were designed and synthesized by connecting donor and acceptor moieties through alkyl spacer. In these design strategy we have chosen carbazole as electron rich and imidazole as electron deficient with deferent functional black (phenyl and phenyl substituted) at the N1 position of imidazole moiety. All the fluorophores were structurally confirmed by spectroscopic methods (NMR, MASS, and FTIR). The photophysical, electrochemical and electroluminescence properties were thoroughlyexamined. All the fluorophores showed good thermal stability and near-UV emission with high photoluminescence quantum yield (PLQY)of ~59% in the solid state. All the synthesized compounds feature Commission International de L'Eclairage (CIE) coordinates of y < 0.08 for a particular doping concentration, which is very close to the National Television Standards Committee (NTSC) standard blue (0.14, 0.08). Solution-processed organic light emitting diode (OLED) device consisting of molecule BIPOCz displays a maximum external quantum efficiency EQE of 1.9% with CIE coordinates of (0.17, 0.07). All these results reveal that this work provides novel approaches for realizing ultra-deep-blue emission with high performance. Graphical abstract: Imidazole-Alkyl spacer-Carbazole (BIPOCZ) based emitter serve as a fluorescent emitter to transmit pure blue light EL emission with CIE coordinates of (0.17. 0.07) and EQE of 1.9% in organic light emitting diodes (OLEDs), which are very crucial for high-quality flat panel display and solid-state lighting. Image 1 Highlights: A series of fluorescent emitters based on Imidazole-spacer-Carbazole were designed and synthesized. All the fluorophores showed good thermal stability and near-UV emission. HOMO and LUMO separation endows them with good carrier transporting property. OLED device consisting of BIPOCz displays an EQEmax of 1.9 % with CIE coordinates of (0.17, 0.07).